Penambahan Kacang Merah dalam Pembuatan Getuk Lindri sebagai Penganan Tinggi Serat - Annisa Putri Wulandari; Agung Arif Gunawan; Tirta Mulyadi; Miratia Afriani (Yayasan Literasi Sains Indonesia, 2025)
Getuk lindri is a traditional Indonesian food made from cassava, know for its sweet taste and soft teksture. This study to esplore the potential of adding red kidney beans (Phaseolus vurgaris L.) to getuk lindri as an alternative high fiber snack. Red kidney beans contain various nutrients such as protein, vitamins, minerals, and bioactive compounds like anthocyanins, which function as antioxidants. The method used in this research was an axperimental approach, consisting of four stages of producing getuk lindri:steaming, mashing, mixing with additional ingredients steamed and mashed before, then mixes with cassava as the main ingredient of getuk lindri. Product evaluation was carried out through organoleptic testing by panelists, including hedonic and hedonic quality assessments of taste, color, aroma, and ekstur, usung ratio wariation of 20:80, 40:60, 70:30. The results showed that the addition of red kidney beans not only increased the fiber content of the product but was also acceptable in terms of organoleptic characteristics. Become a functional foof innovation based on local ingredients that is bots healthy and high in fiber.